Initiation of Sekolah Sadar Gizi by conducting nutritional status assessment and nutritional education to junior high school student - Siti Helmyati; Emy Huriyati; Setyo Utami Wisnusanti; Maria Wigati (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
School is a strategic place to form nutrition behaviors of the students, for example, is by initiating Sekolah Sadar Gizi (Nutrition Awareness School). The first step to initiate Sekolah Sadar Gizi is collecting the nutrition situation data of the students. Nutrition education and nutritional status assessment are examples of how the data can be collected. This is a community services program aimed to provide the nutrition situation of the students and to educate the students to initiate Sekolah Sadar Gizi. The activities were conducted in August – October 2017 at Muhammadiyah 3 Junior High School. There were 2 main activities, nutritional status assessment, and nutrition education. The results show that over-nutritional and under-nutritional problem happened in all classes, either class 7, 8, or 9. The highest number of stunted and obese children is in class 8 which was around 7% and 15%. Meanwhile, the number of wasted children was around 5% and obese children were around 20%. From nutrition education which followed by Palang Merah Remaja of the school, the score of 60% of the participants was increasing. Considering the burden of nutritional problems in the school, initiation of Sekolah Sadar Gizi is highly recommended.